Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/pc.26957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tamarindus indica seed nano‐powder on properties of Luffa cylindrica (L.) fruit waste fiber reinforced polymer composites

Abstract: The aim of this investigation is to determine the physical, mechanical, water absorption behavior, and thermal properties of Tamarindus indica seed powder (TISP) incorporated Luffa cylindrica fruit (LCF) waste fiber reinforced epoxy composites. TISP of size 40–50 nm was mixed with matrix in various weight proportions (2.5, 5.0, 7.5, and 10 wt%), and the composite laminates were made using the manual stacking followed by compression molding technique. The developed composite samples were subjected to various te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…This is a result of both stress transfer from the matrix phase to the fiber and uniform TISP distribution across the laminate. [ 123 ] Poplar seed fibers and polycaprolactone (PCL) were used in the fabrication of composites, the composite. The composite material created under the ideal processing conditions had a sound absorption coefficient higher than 0.7 and a broad sound absorption frequency spectrum.…”
Section: Materials Selection Criteriamentioning
confidence: 99%
“…This is a result of both stress transfer from the matrix phase to the fiber and uniform TISP distribution across the laminate. [ 123 ] Poplar seed fibers and polycaprolactone (PCL) were used in the fabrication of composites, the composite. The composite material created under the ideal processing conditions had a sound absorption coefficient higher than 0.7 and a broad sound absorption frequency spectrum.…”
Section: Materials Selection Criteriamentioning
confidence: 99%
“…Te fbres that take up the load from the matrix are distributed uniformly. Furthermore, a higher amount of reinforcement may lead to agglomeration [40].…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…From all the major investigations, it is found that the 40 wt% FRCs exhibit enhanced mechanical properties. [22][23][24][25][26] Thus, it gives a clear-cut view of combining the nanofiller with the polymer for improving the performance of the developed composites. So, the current research was undertaken to assess the impact of Acacia concinna seed powder (ACSP) and Vachellia nilotica seed powder (VNSP) on the physical, mechanical, and water absorption properties of developed short Turkish hemp (STH) fiber composites.…”
Section: Introductionmentioning
confidence: 99%